ACL Revision in Synthetic ACL graft failure. Issue 1 (31st January 2017) - Etcheto, H. Rivarola; Zordán, J.; Escobar, G.; Collazo, C.; Palanconi, M.; Autorino, C.; Salinas, E. Alvarez
The development of synthetic grafts as an alternative to biological grafts for reconstruction of the anterior cruciate ligament dates from 1980. The interest is awakened due to the potential advantages of: The absence of morbidity associated with donor site, and early return to sport. However, this surgical technique has had multiple complications associated with graft: mechanical failures (synthetic graft failure, loss of fixation), synovial foreign body reaction, recurrent stroke, recurrent instability and ultimately, early osteoarthritis. Objectives: We describe the synthetic graft failure LCA, intraoperative findings and details of surgical technique. Methods: Patient 35 years old, with a history of ACL reconstruction four years of evolution in another health center, consultation with the Service knee arthroscopy for acute knee pain left knee during secondary sporting event to a rotation mechanism with fixed foot. On physical examination, presents and positive Lachman maneuver Pivot. Radiografia in a widening of the tibial tunnel is observed. NMR shows a discontinuity of fibers of synthetic graft. Results: First time arthroscopic revision where synthetic plastic LCA identifies with Disruption fiber pattern. Intraoperatively, hypertrophic chronic synovitis localized predominantly in intercóndilo is observed. debridement thereof is performed, and proceeds to the extraction of the synthetic ligament. Then he was made prior cruentado and revival of the edges of the tunnel, filling them with non-irradiated structural bone allograft. At four months as planned and after confirmation by studies incorporating bone graft was performed the second time with the new plastic ACL. It was planned like a primary graft surgery with autologous hamstring prepared in fourfold form, and fixation with modified transtibial technique Biotransfix system proximal and distal screw Biocomposite (arthrex®). A quadruple graft 9 mm was obtained, making good positioning of tunnels and stable fixation. Conclusion: While ACL reconstruction with synthetic graft has favorable medium-term results, the proportion of patients with complications of irreversible nature and high rates of dissatisfaction in the long term we are inclined to dismiss the indication of this technique in primary ACL reconstruction, to despite the potential benefits it offers.